Transcutaneous spinal direct current stimulation induces lasting fatigue resistance and enhances explosive vertical jump performance - Berry, Helen R.; Tate, Rothwelle J.; Conway, Bernard A. (PloS one, 2017)
Transcutaneous spinal direct current stimulation (tsDCS) is a non-invasive neuromodulatory intervention that has been shown to modify excitability in spinal and supraspinal circuits in animals and humans. Our objective in this study was to explore the functional neuromodulatory potential of tsDCS by examining its immediate and lasting effects over the repeated performance of a whole body maximal exercise in healthy volunteers. Using a double-blind, randomized, crossover, sham-controlled design we investigated the effects of 15 min of anodal tsDCS on repeated vertical countermovement jump (VCJ) performance at 0, 20, 60, and 180 minutes post-stimulation. Measurements of peak and take-off velocity, vertical displacement, peak power and work done during countermovement and push-off VCJ phases were derived from changes in vertical ground reaction force (12 performance parameters) in 12 healthy participants. The magnitude and direction of change in VCJ performance from pre- to post-stimulation differed significantly between sham and active tsDCS for 7 of the 12 VCJ performance measures (P < 0.05). These differences comprised of a post-sham fatigue in VCJ displacement/work done, peak to peak power and take-off velocity, and a resilience to this fatigue effect post-active tsDCS. In addition there was also an enhancement of countermovement performance and total work done (P < 0.05). These changes did not vary across repeated VCJ performances over time post-tsDCS (P > 0.05). Our original findings demonstrate that one single session of anodal tsDCS in healthy subjects can prevent fatigue and maintain or enhance different aspects of whole body explosive motor power over repeated sets of VCJs performed over a period of three hours. The observed effects are discussed in relation to alterations in central fatigue mechanisms, muscle contraction mode during jump execution and changes in spinal cord excitability. These findings have important implications for power endurance sport performance and for neuromotor rehabilitation.